R&D activities and technical information flow in Japanese electronic corporations - Ulrike Görtzen (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 1997)
The paper analyzes R&D-activities of Japanese electronic corporations in the context of the firm's performance for the period 1986 to 1996. Compared to the R&Dexpenditures- to-sales ratio the profit-on-sales ratio is remarkably low for the whole industry. This stresses the problems which the electrical machinery is facing in a time of growing diversification, extremely high costs for new developments and stiff competition with non-patent-protected products. – – Die Studie untersucht die FuE-Aktivitäten von japanischen Elektrounternehmen in Zusammenhang mit dem Erfolg der Unternehmen im Zeitraum von 1986 bis 1996. Auffällig ist, daß die Umsatzrendite verglichen mit den FuE-Ausgaben in Prozent vom Umsatz bei allen Unternehmen erstaunlich niedrig ist. Das verdeutlicht die Probleme, mit denen diese Branche in einer Zeit zunehmender Diversifikation, extrem hoher Kosten für neue Produktentwicklungen und hartem Wettbewerb im Bereich von nicht patentierten Produkten zu kämpfen hat.
Keywords: 330